Perjuangan Perempuan dalam Novel Perempuan di Titik Nol Karya Nawal El-Saadawi: Kajian Feminisme - Suprapto, Suprapto; Setyorini, Adelya Hesty (RUANG KATA: Journal of Language and Literature Studies, 2023)
This study aims to fight for women's rights where the actions in it no longer respect the presence of women at that time. The story takes place in the novel Perempuan Di Titik Zero by Nawal El-Sa'adawi. Apart from that, the aim of this study is to identify the image of women in the novel. In order to achieve the above targets, this study uses a qualitative descriptive method. Based on the results of the analysis, researchers found that the injustice that occurred to the main character of this novel occurred before marriage, during marriage and after marriage. These forms of injustice are all behavior that can cause pain, suffering, especially to women, whether in the form of physical, mental or sexual neglect, including threats, coercion or deprivation of liberty. The results of this study are very useful in making everyone aware that women are the same, have rights that must be fulfilled, must be respected and not looked down upon. Keywords: Feminism, violence, women's role